Online multimedia advertising techniques and technologies - Hua, Xian-Sheng, 1973-; Mei, Tao, 1978-; Hanjalic, A.; IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2011)
"This book unites recent research efforts in online multimedia advertising and includes introductions to basic concepts and fundamental technologies for online advertising, basic multimedia technologies for online multimedia advertising, and modern multimedia advertising schemes, theories and technologies"--Provided by publisher.
1. Click-through rate estimation for rare events in online advertising / Xuerui Wang ... [et al.] -- 2. Reinforcement learning for online optimization of banner format and delivery / Benoit Baccot, Romulus Grigoras, Vincent Charvillat -- 3. Utilizing sentiments in online contextual advertising / Tanveer Siddiqui -- 4. In-image advertising / Lusong Li, Xian-Sheng Hua -- 5. Argo / Xin-Jing Wang ... [et al.] -- 6. The advent of play and pursuit / Yasmin Ibrahim -- 7. Content and attention aware overlay for online video advertising / Huazhong Ning ... [et al.] -- 8. An explorative study of virtual product placement / Chia-Hu Chang, Ja-Ling Wu -- 9. Adapting online advertising techniques to television / Sundar Dorai-Raj ... [et al.] -- 10. Linking traditional TV advertising to Internet advertising / Ling-Yu Duan ... [et al.] -- 11. Contextual in-stream video advertising / Tao Mei, Shipeng Li -- 12. Behavioral targeting online advertising / Jun Yan ... [et al.] -- 13. Distributed technologies for personalized advertisement delivery / Dorothea Tsatsou ... [et al.] -- 14. Audience intelligence in online advertising / Bin Wang -- 15. Targeted mobile advertisement in the IP multimedia subsystem / C. Tselios ... [et al.].
Includes bibliographical references.
Also available in print.
Mode of access: World Wide Web.
Description based on title screen (IGI Global, viewed Mar. 24, 2011).
Keywords: Internet advertising; Internet marketing; Multimedia systems; Adapting online advertising techniques to television; Audience intelligence in online advertising; Click-through rate estimation advertising; Content and attention aware overlay for online video; Contextual in-stream video advertising; Intelligent advertising; Online optimization of banner format and delivery; Personalized advertisement delivery; Targeted mobile advertisement; Virtual product placement; Electronic books